Unlocking the fog: assessing fog collection potential and need as a complementary water resource in arid urban lands–the Alto Hospicio, Chile case - Carter, Virginia; Verbrugghe, Nathalie; Lobos-Roco, Felipe; del Río, Camilo; Albornoz, Francisco; Khan, Ahmed Z. (Frontiers in Environmental Science, 2025)
Water scarcity is a rising issue in fast-growing cities in arid lands, where demand outpaces supply. This leads to non-renewable water systems and exacerbates social inequalities. This is the case for Alto Hospicio (AH), located in the northern Chilean Atacama Desert. Regarding its water availability, the main source of drinking water comes from underground aquifers, last recharged about 10,000 years ago. Nevertheless, atmospheric water such as fog, is present in this territory and offers an alternative, though its potential in large urban areas remains unexplored. This study assesses the fog water collection potential in AH and its surroundings using two methods: in-situ data collection using Standard Fog Collectors (SFCs) and the AMARU model, which estimates fog collection in space and time. This research concludes that fog water collection is feasible in the northeast and southeast areas surrounding the city, where fog collection rates reach up to 10 L m−2 day−1. Fog water has the potential to serve as an effective alternative water source for populations lacking access to drinking water from a public water source, and for activities such as irrigation of urban green spaces, human consumption, and hydroponic farming. Key recommendations for policymakers include incorporating atmospheric water into local city policies, promoting further research on estimating the fog water potential in the AH metropolitan zone, and rethinking water management strategies from nonconventional resources.